Learning in Covid-19 Pandemic: Phenomenological Study on Student's Experience - Muhammad Atmadio Ceisario; Saiful Amien; Dina Mardiana (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2022)
The Covid-19 pandemic changed the learning atmosphere in Indonesia and over the world, from offline to online. Lecturers and students inevitably had to accept the change in learning direction imposed by the government to avoid the ferocity of the pandemic. This study aimed to describe the online learning experience of three Islamic Religious Education students through a phenomenological approach. The authors collected the data through in-depth interviews, transcribed it verbatim into a solid description, and analyzed it through descriptive-psychological phenomenology procedures. This research showed that online learning was an interesting experience at the beginning of the Covid-19 pandemic. However, it ended up disappointing because it was not optimal and ineffective, constrained by many obstacles, and expensive. More than that, the fatal impact for students was learning loss characterized by stress, loss of learning motivation and decreased knowledge/skills due to learning outputs. The results of this study recommended that educational policymakers, education practitioners, and parents should make efforts to assist students so they can get out of the learning loss phenomenon after the pandemic has passed.